ANALISIS MODEL KURIKULUM PENDIDIKAN AGAMA ISLAM DI ABAD 21 - Zakariyah Zakariyah; Muhamad Arif; Nurotul Faidah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
The Islamic religious education curriculum model in the 21st century underwent significant changes, especially in the massive 21st century by collaborating between the education curriculum and technology. This fact is based on the many researches that have been published with an emphasis on the Islamic religious education curriculum model. In line with the above situation, the researcher will conduct an in-depth analysis of several research results. The focus of this research problem is how to model the Islamic religious education curriculum in the 21st century. The research uses a qualitative method with a systematic literature review approach. Sources of research data using search results on Google Scholar, Publish and Perlish and Garuda Ristekbrin with a vulnerability of the last 5-7 years with the keywords